Mathematics anxiety playback - Hannula, Markku; Taskinen, Jaana; Kärkkäinen, Tero; Lassila, Tuula (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
Applied theatre is one method to help people address their emotional issues. In this article we report of a playback theatre in a vocational institute where professional actors performed students’ stories about their life as students and presented them on stage. One of the plays was about mathematics anxiety in a test. In our analysis of the performance, we identified a variety of physiological and psychological effects of the anxiety, such as worrying, attending to other students in the test, feeling tense, and not being able to think clearly. In our reflection, we see the playback theatre being able to present a realistic presentation on anxiety, capturing several aspects of it in a way that students seemed to relate to.